Parental attitudes and expectations towards receiving genomic test results in healthy children. Issue 1 (29th January 2018) - Kulchak Rahm, Alanna; Bailey, Lindsay; Fultz, Kara; Fan, Audrey; Williams, Janet L; Buchanan, Adam; Davis, F Daniel; Murray, Michael F; Williams, Marc S
Abstract : Parents of healthy children enrolled in a biobank want genomic information returned for medically actionable conditions for their child, including conditions that will not manifest until adulthood. Abstract: Little evidence is available to guide returning genomic results in children without medical indication for sequencing. Professional guidelines for returning information on adult-onset conditions are conflicting. The goal of this study was to provide preliminary information on parental attitudes and expectations about returning medically actionable genomic results in children who have been sequenced as part of a population biobank. Four focus groups of parents with a child enrolled in a population biobank were conducted. A deliberative engagement format included education about professional guidelines and ethical issues around returning results to children. Parents were presented two scenarios where their healthy child has a pathogenic variant for: (a) a medically actionable childhood condition; (b) a hereditary cancer syndrome with no medical management until adulthood. Thematic analysis was conducted on verbatim transcripts. Regardless of the scenario, parents stated that the genomic information was important, was like other unexpected medical information, and disclosure should be tailored to the child's age and result. Parents wanted the results in their child's medical record. Reasons for learning adult-onset results in their healthy children included to prepare their child for necessary medical action in adulthood. Parents also provided suggestions for program design. This preliminary evidence suggests that parents desire genomic results and expect to use this information to protect their child's health. More empirical research on psychosocial adjustment to such information with continued engagement of parents and children is needed to further inform how to best support families in the communication and use of genomic information.